Ordem e Progresso, Civilização e Barbárie. Perón, Vargas e Positivismo. (Argentina-Brasil, 1930-1955) Order and Progress, Civilization and Barbarity. Perón, Vargas and Positivism. (Argentina-Brazil, 1930-1955) (PerCursos, 2007)
Palavras-Chave: